(untitled) (Chest & Heart Journal, 2021)
Asthma needs continuous attention. Main problem in asthma lies in airway of the lung. Symptoms depend on degree of airway inflammation.But the tragedy is that, despite the high quality of available medications and treatment regimens that are being simplified on a regular basis, asthma is still not sufficiently controlled in many cases.World-wide, it is estimated that 300 million people are affected with bronchial asthma and of all asthma patients, 50% have symptoms on a daily basis and almost all patients report limitations to daily activities1.So it is very important to search for any pitfall meticulously and try to solve it out. Here we will discuss some aspect of pitfall of asthma management. Chest Heart J. 2020; 44(1) : 48-51